Evaluation of the CIPP Model on the Merdeka Curriculum at SMP 2 Palembayan - Susanto, Arino; Kardena, Absharini; Elpayani, Elpayani (EDUMALSYS Journal of Research in Education Management, 2024)
By using of the CIPP evaluation model of SMP 2 Palembayan, this research seeks to study the application of the CIPP (Context, Input, Process, Product) evaluation model, students learning outcomes in the field of English. This test is a subjective exploration that uses the CIPP model by assessing each part of the setting, information, interactions, and items to achieve a continuously evolving experience. English teachers, curriculum representatives, and the principal at SMP 2 Palembayan served as the data sources for the study. Observation instruments were used to collect primary data, and interviews and photographs were used to collect secondary data. After that, the observation data was analyzed quantitatively, while the interviews and data analysis were analyzed descriptively and qualitatively. The results showed that the conditions for implementing learning and learning activities at SMP 2 Palembayan were said to be very effective when learning was carried out.